LAUDATIO. DEDICATED TO PROFESSOR FLORIN DAN IRIMIE ON HIS 65ᵀᴴ ANNIVERSARY - TOȘA, Monica Ioana; POPPE, László; PAIZS, Csaba (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Professor Florin Dan Irimie was born on March 30th, 1953 in Brașov, where he completed his primary, gymnasium and high school studies. In 1972, he became a student of the Faculty of Chemistry and Chemical Engineering of the Polytechnic University of Iași, specializing in Technology of Organic Compounds. He elaborated his diploma project under the guidance of the famous Professor Corneliu Oniscu and he graduated in 1977. During 1997-1982, he was employed as a chemical engineer at the Farmec Factory of Cosmetic Products in Cluj-Napoca, first as a coordinator of production activity, afterwards as a researcher of the Research and Development Department. In the period of 1982-1987 he performed research as a chemical engineer at the Biochemistry Department of the University of Agricultural Sciences from Cluj-Napoca. In 1987 he was invited as a teaching assistant to Babeș-Bolyai University (UBB), Faculty of Chemistry and Chemical Engineering to hold Chemical Technology seminars and laboratory works.